A novel gene, GCRG224, is differentially expressed in human gastric mucosa - Wang, Gang-Shi (World J Gastroenterol, 2003)
AIM: To clone genes that may predispose us to human gastric cancer and to analyze it’s expression in gastric tissues. METHODS: Specimens of paired tumor, paratumor and normal gastric mucosa tissues collected from fifteen patients who suffered from stomach antrum adenocarcinoma were used for analysis. Seven out of the fifteen cases were first studied by fluorescent differential display reverse transcription polymerase chain reaction (DDTR-PCR) analysis. The differentially expressed bands of interest were cloned, analyzed by Northern blot, sequencing and RT-PCR. Through BLAST, the sequencing results were compared with GenBank database for homology analysis. In situ hybridization with DIG-labeled cRNA probes was used to analyze the expression of interesting cDNA bands in paraffin embedded paired normal gastric mucosa and cancer tissues isolated from 30 gastric adenocarcinoma patients. RESULTS: DDRT-PCR showed that one of the interesting cDNA bands, which was named W2, expressed much higher in all seven tested tumor and paratumor samples than in their normal counterparts, it was sub-cloned into a pGEM-T Easy vector. Two subclones were subsequently obtained. One of the subclone, GCRG224, was studied further. The sequencing result showed that GCRG224 consisted of 1159 base pairs and had one open reading frame (ORF). It located at human chromosome 11q14. No homologue was found in GenBank database with GCRG224-ORF. This nucleotide sequence data were submitted to GenBank with accession No. AF438406. RT-PCR showed that GCRG224 expressed higher in 11/15 gastric cancer tissues than in non-tumor tissues. However, the result of Northern blot analysis showed a higher GCRG224 expression in the non-tumor tissue than in the tumor one. Human multiple tissue Northern blot analysis revealed that GCRG224 also expressed in human normal colon tissue, and peripheral blood leukocyte. In situ hybridization analysis showed that only 5/30 adenocarcinoma, 3/18 dysplasia and 6/18 intestinal metaplasia showed higher GCRG224 expression level than the normal gastric glands. However, GCRG224 was over-expressed predominantly in 26/30 cases of normal mucosal epithelium. CONCLUSION: A novel gene named GCRG224 was identified from human gastric mucosal tissue. It overexpressed in almost all gastric mucosal epithelium but only a small portion of cancer and precancerous leisions. The role of GCRG224 expression in gastric epithelium needs further study.